(untitled) (Journal of Social Sciences Review, 2022)
Male and female students’ choices always matter when it comes to the selection of any profession or any kind of strategy that is why our study is of supreme importance. This study was conducted to make sure that male students select different learning strategies for their lecture than female students and vice versa. The study was conducted in the Department of Education at the University of Loralai in Balochistan. It was a descriptive (a type of quantitative) research design for which participants were randomly selected through a simple random selection technique. For gender-wise comparison, 101 were male while 56 were female students who filled out and returned the questionnaires. The scale adopted by us from Jimenez et al. (2018) had 17 items in total which were spread in three dimensions i.e., micro-learning strategy (MLS; 05 items; α=0.83), keys for memory and metacognition learning strategy (KMMLS; 05 items; α= 0.65) and emotional social support learning strategy (ESSLS; 07 items; α= 0.61). The total Cronbach α of the scale was also in a highly acceptable range (α=0.84) achieved through running a pilot study of 09 respondents. For validation of the scale, we relied on factor analysis run in previous studies (e.g., Jimenez et al. 2018). The results proved that the students had to use always all three types of learning strategies when they have to learn their lectures. Upon testing of hypotheses, significant differences were found only in the keys for memory and metacognition learning strategy, and overall learning strategies, which further revealed that males had higher mean scores than female students. It then concludes that male students prefer cognitive learning strategies for lecture learning. The results were discussed in the views of current and past literature and suggestions were given based on the results.